Experimental study and numerical simulation of the kinetic energy recovery of the mine's exhaust gas. (2nd December 2021) - Jiang, Yefeng; Li, Xiaochuan; Xiang, Wu; Wang, Li; Liu, Pinwei; Li, Jiawei
ABSTRACT: In mines, the exhaust gas is mainly discharged from main ventilators in free dissipation state. The effective recovery of its kinetic energy is lucrative from economical and technical standpoints. This study is focused on recovering the kinetic energy of the exhaust gas without deteriorating the main ventilator's safe operation or increasing power dissipation. The related experiments and numerical simulations were performed for the conical diffusers with diffusing angles of 16° and inlet diameters of 220 and 320 mm, respectively. By examining the start-up and operation states of the wind turbines using inlet collectors with conical, circular arc, and cone-arc shapes, it was found that the wind speed at the inlet of the drainage tube exceeded 4 and 20 m/s at the minimal and maximal distances from the wind turbine, respectively. The wind speed at the overflow tube outlet was no less than 1.8 m/s, proving a certain recovery of kinetic energy by the wind turbine. Thus, the critical distance between the diffuser and the inlet collector should be at least four times the diffuser's inlet diameter. Finally, the velocity, pressure, and flow fields in the vortex core regions of the kinetic recovery system with different types of inlet collectors were simulated with the FLUENT commercial software package. The simulation results revealed that the circular-arc collector outperformed other three tested configurations in kinetic energy recovery. Implications : This study is focused on recovering the kinetic energy of the exhaust gas without deteriorating the main ventilator's safe operation or increasing power dissipation. China is a country with coal as its main energy source, which releases over ten billion cubic meters of the exhaust gas annually. In addition to low-concentration methane, there is also the exhaust gas released at a velocity of about 20 m/s, which kinetic energy recovery would be very lucrative. The significance of this study is that the mine's main ventilator outlet was simplified as two conical diffusers with parameters α =16°/ n =2 and α =16°/ n =2.5, and the optimal critical distance between the diffuser and the collector was determined as 4 Di, where Di was the diffuser's inlet diameter. Under that optimal condition, the system can achieve the maximum power without affecting the ventilator's normal operation. It is instructive to make full use of and manage the exhaust gas in mine that fits the journal on the purpose of air waste management. Finally, we provide a statement serious that the article is original and unpublished and is not being considered for publication elsewhere.